Quantitative Spectrophotometric Estimation of Famotidine Using Hydrotropic Solubilization Technique - Maheshwari, R.K.; Shankar Shukla, Ravi (Asian Journal of Chemistry, 2010)
In the present investigation, 1.5 M metformin hydrochloride, (an economic drug) solution, was employed as hydrotropic solubilizing agent to solubilize poorly water-soluble drug, famotidine, for its UV analysis. Proposed method is new, simple, environmentally friendly, accurate and reproducible. Accuracy, reproducibility and precision of the proposed method was validated statistically.